Smart meter based on IoT platform - Mohd Yunus, Muhammad Sharir Fathullah; Yusoff, Siti Hajar; Mohd Sapihie, Siti Nadiah; Razali, Nur Syazana Izzati (IEEE, 2023)
The manual nature of the classic energy meter has rendered it useless in the Internet of Things (IoT) era. It is not only a waste of time, but it is also not systematized. The traditional energy metering method is cumbersome and inefficient. A creative and essential solution is necessary to keep up with technological changes. This aligns with Malaysia's vision of becoming a developed country by 2020. The introduction of smart meters has completely changed how energy is measured. Smart meters automate procedures and increase efficiency throughout the entire system. Utility workers no longer need to visit each house to collect energy consumption data for billing purposes. Smart meters, on the other hand, give consumers access to real-time data on energy consumption, enabling them to monitor and manage their electricity usage. The goal of this project is to create a smart meter that is just as functional as other smart meters on the market with faster time intervals as the market smart meter takes 30 minutes to update real-time data. The proposed smart meter, which is built on an IoT platform, automates the entire process by sending data to the utility provider via IoT technology and obviating the need for in-person visits. The utility company can then analyze the data and generate accurate bills for each user. The design will also integrate extra functions like meter tampering detection. Hardware development, programming, and circuit design are all included in this project. With Arduino Uno serving as the system's microprocessor, the smart meter will operate effectively and dependably.